2020
DOI: 10.1017/s0266467420000036
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal patterns of large-seeded plants and the foraging behaviour of a frugivorous bat

Abstract: Mutualistic interactions are biologically important, diverse and poorly understood. Comprehending these interactions and the effectiveness of the mutualistic partners has been the central focus of ecological and evolutionary studies, as this task requires disentangling the pieces of mutualism under study. Here, we tested the hypothesis that feeding activity of Artibeus phaeotis influences density, diversity and distance effects of the seed rain of large-seeded plant species in a Neotropical dry forest of Costa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…However, there is still little empirical data about bat seed dispersal distances, especially in open formations such as grasslands or urban areas, where these distances can be greater due to the larger distance between trees (Abedi‐Lartey et al., 2016). Studies that find feeding roosts using radio tracking tend to find larger dispersal distance values (Morrison, 1978; Villalobos‐Chaves et al., 2020), which can be related to minimal dispersal distance underestimation due to feeding roosts sampled through active searches (Seltzer et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still little empirical data about bat seed dispersal distances, especially in open formations such as grasslands or urban areas, where these distances can be greater due to the larger distance between trees (Abedi‐Lartey et al., 2016). Studies that find feeding roosts using radio tracking tend to find larger dispersal distance values (Morrison, 1978; Villalobos‐Chaves et al., 2020), which can be related to minimal dispersal distance underestimation due to feeding roosts sampled through active searches (Seltzer et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Clump‐dispersal of cashew and areca was commercially more valued by people than scatter‐dispersal. Dispersal of large seeds (like that of cashew and areca) by bats at high densities occurs typically at short distances from feeding sites (Seltzer et al 2013, Villalobos‐Chaves et al 2020), which would have facilitated effective tracking of seeds and easy collection by people. In isolated plantations, this effect could be magnified both due to short dispersal distances and concentrated bat densities, which reflected in the more positive perceptions of respondents associated with isolated plantations in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that flying foxes or fruit bats (Djossa et al, 2008;Corlett, 2017;Villalobos-Chaves et al, 2020) and primates (Stevenson et al, 2005;Corlett, 2017;Tsuji, Su, 2018) are seed dispersers for a large number of plant species across the world. They eat large quantities of fruit and disperse seeds.…”
Section: Introductionmentioning
confidence: 99%